Interpretasi nilai Cycle Threshold (CT) Reverse Transcriptase-Polymerase Chain Reaction (RT-PCR) SARS-CoV-2 pada pasien hamil dengan uji antibodi SARS-CoV-2 positif dan COVID-19 asimtomatik - Ni Wayan Candrawati; William Ray Cassidy (DiscoverSys Inc., 2021)
Background: The majority of pregnant women with COVID-19 will be asymptomatic throughout the disease period. SARS-CoV-2 antibody tests were utilized as a screening tool for patients giving birth in a hospital. Cycle Threshold (CT) value in asymptomatic pregnant women may guide patient management and isolation protocol.Methods: Research data were obtained from medical records from March until October 2020 with a total sampling method. Pregnant women with positive SARS-CoV-2 antibody and asymptomatic COVID-19 were included. CT-value based on gene primers were grouped and analyzed by Microsoft Excel 365 for Windows.Results: Twenty-five pregnant women with asymptomatic COVID-19 fulfilled the inclusion criteria. All patients had positive SARS-CoV-2 antibodies. The highest and lowest CT-value for the RdRp gene were 37.91 and 26.90, followed by N-gene (34.37 and 32.16), E-gene (38.36 and 27.60), helicase gene (35.65 and 24.29), ORF1a (35.87 and 26.80), and ORF1ab (41.28 and 27.82).Conclusion: SARS-CoV-2 antibody test is not a recommended screening tool as it can reveal past infection or immunity to SARS-CoV-2. CT-value is incapable of determining COVID-19 severity and infection period. Latar Belakang: Mayoritas pasien COVID-19 dengan kehamilan tidak bergejala sepanjang periode perjalanan penyakit. Uji antibodi SARS-CoV-2 sempat digunakan sebagai alat skrining pasien yang akan melahirkan di rumah sakit. Nilai Cycle Threshold (CT) pada pasien hamil dengan COVID-19 asimtomatik kemungkinan dapat memandu tatalaksana dan isolasi pasien.Metode: Penelitian ini menggunakan data sekunder rekam medis dari bulan Maret hingga Oktober 2020 dengan total sampling. Data pasien hamil dengan uji antibodi SARS-CoV-2 positif dan terkonfirmasi COVID-19 asimtomatik dianalisis. Nilai cycle threshold (CT-value) berdasar primer dikelompokkan dan dianalisis menggunakan Microsoft Excel 365 untuk Windows. Hasil: Sebanyak 25 pasien hamil dengan terkonfirmasi COVID-19 asimtomatik memenuhi kriteria inklusi. Seluruh pasien memiliki hasil tes cepat antibodi SARS-CoV-2 reaktif. Nilai CT tertinggi dan terendah untuk gen RdRp sebesar 37,91 dan 26,9, diikuti dengan gen N (34,37 dan 32,16), gen E (38,36 dan 27,60), gen helicase (35,65 dan 24,29), ORF1a (35,87 dan 26,80), dan ORF1ab (41,28 dan 27,82).Simpulan: Nilai CT tidak dapat digunakan sebagai indikator keparahan gejala dan periode infeksi COVID-19. Pasien hamil dengan COVID-19 asimtomatik tidak harus menjalani isolasi di rumah sakit.